2001
DOI: 10.1172/jci10860
|View full text |Cite
|
Sign up to set email alerts
|

Self-antigen–presenting cells expressing diabetes-associated autoantigens exist in both thymus and peripheral lymphoid organs

Abstract: Recent reports indicate that genes with tissue-restricted expression, including those encoding the type 1 diabetes autoantigens insulin, glutamic acid decarboxylase (GAD), and the tyrosine-phosphatase-like protein IA-2 (or ICA512), are transcribed in the thymus. The reported modulation of diabetes susceptibility by genetically determined differences in thymic insulin levels and studies in transgenic mice provide correlative and functional evidence that thymic expression of peripheral proteins is crucial for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 47 publications
11
100
1
1
Order By: Relevance
“…Despite many studies in both rodents and humans to stimulate tolerogenic mechanisms using various protocols of antigen administration with antigens in different pharmaceutical forms (e.g., peptides or whole antigens) and testing diverse administration routes, robust data demonstrating clinical benefits are not yet available (18). Recent studies in mice have also indicated that repeated administration of free antigens can induce fatal autoimmune responses (30). In this context, the ability to target minute amounts of antigens to steady-state immature DCs in vivo has promise as an approach to obtain antigenspecific immunological tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies in both rodents and humans to stimulate tolerogenic mechanisms using various protocols of antigen administration with antigens in different pharmaceutical forms (e.g., peptides or whole antigens) and testing diverse administration routes, robust data demonstrating clinical benefits are not yet available (18). Recent studies in mice have also indicated that repeated administration of free antigens can induce fatal autoimmune responses (30). In this context, the ability to target minute amounts of antigens to steady-state immature DCs in vivo has promise as an approach to obtain antigenspecific immunological tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Many ''tissuespecific'' molecules (55), especially of endocrine organ-related proteins including GAD and insulin (56)(57)(58), are now known to be expressed at low levels in small numbers of thymic medullary epithelial cells under the control of the AIRE gene (59). In AIRE-null mutants, T cells arising spontaneously in the thymus and specific for various self peptides escape thymic negative selection and induce organ-specific autoimmune disease in the periphery (60).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that a number of autoantigens, including those that were believed to be secluded from the immune system, are actually expressed in the thymus [19][20][21][22][23][24][25][26][27]. Furthermore, experiments have proven that such a promiscuous expression of autoantigen would contribute to eliminating pathogenic autoimmune T cells from the T cell repertoire [24,25].…”
Section: Introductionmentioning
confidence: 99%